Upregulation of T‐cell factor‐4 isoform‐responsive target genes in hepatocellular carcinoma. (8th May 2013) - Tomimaru, Yoshito; Koga, Hironori; Yano, Hirohisa; de, Suzanne; Wands, Jack R.; Kim, Miran
Abstract Background The Wnt/β‐catenin signalling pathway regulates genes involved in cell proliferation, survival, migration and invasion through regulation by T‐cell factor (TCF)‐4 transcription factor proteins. However, the role of TCF‐4 isoforms generated by alternative splicing events in hepatocellular carcinoma (HCC) is unknown. Aim Here, we investigated TCF‐4 isoforms (TCF‐4J and K)‐responsive target genes that are important in hepatic oncogenesis and tumour development. Methods Gene expression microarray was performed on HCC cells overexpressing TCF‐4J and K isoforms. Expression level of selected target genes was evaluated and correlations were made between their expression level and that of TCF‐4 isoform in 47 pairs of human HCC tumours. Results Comparison by gene expression microarray revealed that 447 genes were upregulated and 343 downregulated more than 2.0‐fold in TCF‐4J compared with TCF‐4K expressing cells. We validated expression of 18 selected target genes involved in Wnt/β‐catenin, insulin/IGF‐1/IRS1 and Notch signalling pathways in 47 pairs of human HCCs and adjacent uninvolved liver tissues. It was observed that 13 genes (CLDN2, STK17B, SPP1, AXIN2, WISP2, MMP7, IRS1, ANXA1, CAMK2N1, ASPH, GPR56, CD24 and JAG1) activated by TCF‐4J isoform in HCC cells, were also upregulated in HCC tumours compared with adjacent peritumour tissue; more importantly, 10 genes exhibited a significant correlation with the TCF‐4J expression level in tumour. Conclusion TCF‐4 isoforms (TCF‐4J and K) activated different downstream target genes in HCC. The biological consequence of TCF‐4J isoform expression was upregulation of genes associated with tripartite Wnt/β‐catenin, insulin/IGF‐1/IRS1 and Notch signal transduction pathway activation, which contribute to the pathogenesis of HCC.